The current status of aquaculture and aquafeed production in Bangladesh - Mamun-Ur-Rashid, M.; Belton, Ben; Phillips, M.; Karim, M. (2013)
Over the last decade, dramatic increases in the production of a variety of species from commercial aquaculture systems and sharp increases in per capita fish consumption have occurred in Bangladesh. This transition has been made possible by widespread adoption of semi-intensive and intensive production practices, accompanied by growth in the production and use of aquafeeds. Findings relating to the current status of aquaculture in Bangladesh have been reported in greater detail elsewhere. This article provides a brief overview of the status of aquaculture and fish consumption in the country and presents new information on the status of aquafeed production in Bangladesh, drawn from a recent study of the aquafeed industry. This article is based on key findings of a report published by WorldFish on the status of aquaculture and fish consumption in Bangladesh and presented at the AQUA 2012 conference in Prague.